Biomechanical Evaluation of Unilateral Versus Bilateral C1 Lateral Mass-C2 Intralaminar Fixation. (May 2017) - Bhatia, Nitin; Rama, Asheen; Sievers, Brandon; Quigley, Ryan; McGarry, Michelle H.; Lee, Yu-Po; Lee, Thay Q
Study Design: Biomechanical, cadaveric study. Objectives: To compare the relative stiffness of unilateral C1 lateral mass-C2 intralaminar fixation to intact specimens and bilateral C1 lateral mass-C2 intralaminar constructs. Methods: The biomechanical integrity of a unilateral C1 lateral mass-C2 intralaminar screw construct was compared to intact specimens and bilateral C1 lateral mass-C2 intralaminar screw constructs. Five human cadaveric specimens were used. Range of motion and stiffness were tested to determine the stiffness of the constructs. Results: Unilateral fixation significantly decreased flexion/extension range of motion compared to intact ( P < .001) but did not significantly affect axial rotation ( P = .3) or bending range of motion ( P = .3). There was a significant decrease in stiffness in extension for both unilateral and bilateral fixation techniques compared to intact ( P = .04 and P = .03, respectively). There was also a significant decrease in stiffness for ipsilateral rotation for the unilateral construct compared to intact ( P = .007) whereas the bilateral construct significantly increased ipsilateral rotation stiffness compared to both intact and unilateral fixation ( P < .001). Conclusion: Bilateral constructs did show improved biomechanical properties compared to the unilateral constructs. However, unilateral C1-C2 fixation using a C1 lateral mass and C2 intralaminar screw-rod construct decreased range of motion and improved stiffness compared to the intact state with the exception of extension and ipsilateral rotation. Hence, a unilateral construct may be acceptable in clinical situations in which bilateral fixation is not possible, but an external orthosis may be necessary to achieve a fusion.